Water Oxygen Consumption Rather Than Sediment Oxygen Consumption Drives the Variation of Hypoxia on the East China Sea Shelf. Issue 2 (18th February 2022) - Meng, Qicheng; Zhang, Wenyan; Zhou, Feng; Liao, Yibo; Yu, Peisong; Tang, Yanbin; Ma, Xiao; Tian, Di; Ding, Ruibin; Ni, Xiaobo; Zeng, Dingyong; Schrum, Corinna
Abstract: Sediment oxygen consumption (SOC) is important in modulating the oxygen budget in the East China Sea where seasonal hypoxia occurs. Porewater advection, molecular diffusion and bioturbation supply oxygen for sedimentary organic matter degradation. A pelagic‐benthic coupled model was applied to quantify the SOC. A comparison with observations showed good model performance in reproducing the hydrographic and ecological environments, particularly for the interannual variation in the hypoxic zone. Simulation results show that porewater‐advection‐induced flux is the predominant component of the SOC in sandy areas on the Changjiang bank and outer shelves, while the bioturbation‐induced flux is predominant at mud depocenters. By comparing SOC to the water oxygen consumption (WOC) below the pycnocline, the contribution of SOC is generally below ∼40% in the hypoxic zone. The spatial distribution of SOC in summer is relatively steady from year to year, while the high WOC patches explain more about the interannual variation in the hypoxic zone. WOC rather than SOC drives the variation of hypoxia. Particularly on the Changjiang bank, milder hydrodynamics are favorable for both the higher WOC and bioturbation‐induced benthic oxygen flux but substantially suppress the porewater advective flux, which results in the net lower contribution of SOC to hypoxia. This finding may shed light on other pelagic‐benthic coupling processes in coastal shelf seas where hypoxia occurs on permeable sediments. Plain Language Summary: Oxygen exhaustion or hypoxia issues have been increasingly found in coastal waters. The seasonal hypoxic zone off the Changjiang Estuary in the East China Sea is one of the largest coastal hypoxic zones worldwide. It is of significance to understand the underlying drivers of its formation as well as its variation. The oxygen extracted from the water‐sediment interface has been realized to be an important de‐oxygenation way. Porewater flow, molecular diffusion and macrobenthos reworking facilitate sediment oxygen consumption in deeper layers. We used a model to simulate the three‐dimensional sediment interacting with the water column. We found that although the sediment oxygen consumption showed great spatial heterogeneity and complex temporal variations, its pattern did not change much in each summer relative to the highly variable hypoxic zone. Sediment oxygen consumption is not the major driver of the variation of hypoxia. Nevertheless, it has complex variations coupled with the pelagic system in association with hypoxia. Additionally, the buffering effect of the benthic system suggests the challenge of mitigating hypoxia effectively by reducing marine primary production. Key Points: Contributions of porewater advection, molecular diffusion and bioturbation to sediment oxygen consumption in East China Sea are quantified Water oxygen consumption is the major driver of the variation of hypoxia rather than sediment oxygen consumption Mild hydrodynamics increase water oxygen consumption but weaken sediment oxygen consumption by suppressing porewater advection